What Market Structures and Factor Influencing Tuna Exports? (Case Study: Indonesia) - Osmaleli Osmaleli; Hana Hana; Tridoyo Kusumastanto (BIO Web of Conferences, 2023)
Tuna is one of the main exports of fish from Indonesia and has great potential for export. Despite having great potential, Indonesia only ranks second as a tuna producing country in ASEAN. This study aims to (1) examine the structure of Indonesia's international tuna market, and (2) analyze the factors affecting Indonesia's tuna exports in the international market. The research method is secondary data. The methods of analysis are the Herfindahl Hirschman Index (HHI) and Concentration Ratio (CR4), Revealed Comparative Advantage (RCA) and Export Product Dynamic (EPD) and panel data regression. Novelty of this research that the market structure of fresh and frozen tuna is a perfectly competitive market, while canned tuna is an oligopoly. Indonesia's fresh, frozen and canned tuna has strong export competitiveness in the America and Japan as well as Indonesia is a rising star in the America, France and Bulgaria markets for canned tuna products. Analysis of panel regression data proves the variable which affects the value of Indonesia's tuna exports is the export price of tuna fish.